A descriptive study on The Malaysian Parents' HPV Vaccination Intentions / Mohd Rozaimy Ridzuan ... [et al.] - Ridzuan, Mohd Rozaimy; Abd Rahman, Noor Amira Syazwani; Manas, Nur Hidayahtul Nabihah; Rabun, Mohd Nazir; Yew, Ju Soon
Cervical cancer is the second most frequent cancer in low-income countries and the fourth in the world, and it is the most common cancer of the female reproductive organs. In Malaysia, cervical cancer is the second most frequently occurring cancer (after breast cancer) amongst women aged 15 and 44 years. When the whole population is considered, Malaysia's cervical cancer mortality is two-fold higher than countries like the United Kingdom, Finland, and the Netherlands. Despite the free Human papillomavirus (HPV) immunization, acceptance of the vaccination program is not guaranteed as some parents are still against it for various reasons. Hence, this study attempts to identify determinants of parents' HPV vaccination intentions such as attitude, subjective norms, perceived behavioural control, anticipatory regret, and trust in government. This quantitative study used a purposive sampling technique, which meant that only parents or caregivers over 18 with at least one child under 12 were eligible to participate. The sample size of the study is 318 respondents. This study found that all determinants of HPV vaccination intention scored high Mean, and the majority of the parents were willing to vaccinate their children against HPV.